Corporate Social and Financial Performance Re-Examined: Industry Effects in a Linear Mixed Model Analysis - Baird, Philip L. (Journal of business ethics, 2012)
In this research, we shed new light on the empirical link between corporate social performance (CSP) and corporate financial performance (CFP) via the application of empirical models and methods new to the CSP–CFP literature. Applying advanced financial models to a uniquely constructed panel dataset, we demonstrate that a significant overall CSP–CFP relationship exists and that this relationship is, in part, conditioned on firms’ industry-specific context. To accommodate the estimation of time-invariant industry and industry-interaction effects, we estimate linear mixed models in our test of the CSP–CFP relationship. Our results show both a significant overall CSP effect as well as significant industry effects between CSP and CFP. In conflict with expectations, the unweighted average effect of CSP on CFP is negative. Our industry analysis, however, shows that in over 17% of the industries in our sample, the effect of CSP on CFP for socially responsible firms is positive. We also examine the multidimensional nature of the CSP construct in an industry context by exploring the CSP dimension–industry nexus and identify dimensions of social performance that are associated with either better or worse financial performance. Our results confirm the existence of disparate CSP dimension–industry effects on CFP, thus our results provide important and actionable information to decision makers considering whether and how to commit corporate resources to social performance.